Between Mimetic Exacerbation and Abstraction: Images of Atrocity in Contemporary Art - Maganoli, Paolo (Academic Quarter | Akademisk kvarter, 2012)
Pictures of atrocity play a major role in human rights campaigns, but contemporary artists may show different responses to human rights violations. The essay looks at a less discussed strand in contemporary art, which has taken an approach to the representation of human rights violations, i.e. the works of artists and activists Thomas Hirschhorn and Paul Chan. The article asks and answers the question: Ultimately Chan and Hirschhorn’s fascination with violence opens up serious questions regarding the use of images of physical abuse in order to garner interest in the politics of human rights. Is the depiction of violence necessary in order to provoke spectators and induce them to protest against human rights violations or, alternatively, is graphic violence always voyeuristic and a further degradation of the victim?